Diksi Diksi dalam Kumpulan Puisi Sarinah Karya Esha Tegar - Herthalia, Regina Ayu; Andalas, Maharani Intan (Jurnal Sastra Indonesia, 2019)
ABSTRACT Literary works is one form of art in which language is used as a medium, one of them is poetry. Language in poetry is free and solid regarding the licencia poetica, yet it still contains various aspects of life as the poet?s idea. In order to convey his ideas, the poet uses diction on poetry. The usage of dictions on poetry are able to reveal many things, for example, a city. The description of a city through diction within literary works are often depicted through Indonesian poetry. One of those poetry collections which potray a city through diction usage is Sarinah Poetry Collection by Esha Tegar Putra. This research present the usage of dictions within Sarinah Poetry Collection by Esha Tegar Putra. The problems being discussed are (1) how does the diction interpret a city within the Sarinah Poetry Collection by Esha Tegar Putra (2) how is the relation between the diction and other poetry elements contain in Sarinah Poetry Collection by Esha Tegar and (3) how does the meaning contained within Sarinah Poetry Collection by Esha Tegar Putra related to the diction which intepreted city. The approach used in this research is stylictica with qualitative method. The data were obtained from fifteen poems  written in Sarinah Poetry Collection by Esha Tegar Putra. The result of this study showed that within this Sarinah Poetry Collection are carried diction in form of nouns, verbs, dictions with connotative and dennotative meaning, and diction in form of basic words also words that have undergone morphological processes. The usage of the diction based on the word type and the meaning type is aiming more valid interpretation about city, such as name of the places and facilities provided in the city. Based on the form, the usage of the diction within  Sarinah Poetry Collection is working as the element to strengthen the atmosphere withi the poems. the diction contained in this poem are related to other poetry elements such as tone, imagery and figure of speech, so that they could bring a whole unity meaning of the poem. The diction being used by the poet is functioning to reinforce the meaning and the atmosphere, so that the depiction about a trip, traffic jam, bustle, poverty, environmental matters and injustice that represent a city is clearly present. Keywords: Diction, Poetry Collection, Sarinah, Stylistic